MIDDLE MIOCENE DIATOMITE- BEARING FORMATIONS FROM WESTERN ROMANIA - Codrea, V.; Barbu Ο.; Bedelean, H. (Bulletin of the Geological Society of Greece, 2007)
In Western Romania diatomite occurs only in the Lower Sarmatian (Middle Miocene) formations, as a consequence of intense volcanism developed in Apuseni Mountains and evolution of peculiar sedimentary basins connected to the Pannonian realm. The main basins with diatomite successions are Zar and and VadBorod. The diatomite preserves besides diatoms (centric and pennate) and other microfossils (dinoflagellates, ebriidinas, silicoflagellates, phytolites) assemblages a lot of macrofossils as plants (mainly foliar imprints), fish, reptiles and mammals. Several taxa are indicative for environment reconstruction. The Lower Sarmatian climate is estimate as wet warm temperate to subtropical. A tentative of both aquatic and land environments reconstruction is done.